1984
DOI: 10.1002/j.1460-2075.1984.tb02179.x
|View full text |Cite
|
Sign up to set email alerts
|

Encephalomyocarditis virus RNA synthesis in vitro is protein-primed.

Abstract: A crude membrane-bound replication complex isolated from encephalomyocarditis virus-infected ceils is able to initiate the synthesis of viral RNA. Both the formation of the primer, VPg-pU, and its utilization for the initiation of RNA chains take place in this system. A significant amount of the synthesized VPg-pU is found in the free fonn. The predominant product of the de novo initiation is represented by short phenol-soluble VPg oligonucleotide species, and only a smail percentage of the latter appear to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
4
20
0
Order By: Relevance
“…8A; compare lane 2 with lanes 7 and 10, respectively). Essentially all of the results described here with the It has previously been shown that the migration of the uridylylated form of PV1(M) or EMCV VPg (2 kDa) in SDSpolyacrylamide gels is highly aberrant and resembles that of a 7-to 12-kDa peptide (31,48,58,62). The same appears to be true for the migration of the other uridylylated viral VPg's or mutant PV(M) VPg peptides.…”
Section: Fig 3 (A) Nested Set Of Hrv2 Rnas As Templates For Uridylysupporting
confidence: 73%
“…8A; compare lane 2 with lanes 7 and 10, respectively). Essentially all of the results described here with the It has previously been shown that the migration of the uridylylated form of PV1(M) or EMCV VPg (2 kDa) in SDSpolyacrylamide gels is highly aberrant and resembles that of a 7-to 12-kDa peptide (31,48,58,62). The same appears to be true for the migration of the other uridylylated viral VPg's or mutant PV(M) VPg peptides.…”
Section: Fig 3 (A) Nested Set Of Hrv2 Rnas As Templates For Uridylysupporting
confidence: 73%
“…This possibility was supported by the observation that virusinfected HeLa cells contain VPgpUpU, in which VPg is covalently linked to UMP (10). In addition, the synthesis of VPgpU and VPgpUpU could be achieved in vitro by using membranous replication complexes isolated from virus-infected cells (58,59,62). Recently it was directly shown that the RNA polymerase of poliovirus possesses a synthetic activity in vitro that catalyzes the linkage of UMP to the hydroxyl group of tyrosine in VPg, yielding VPgpU and VPgpUpU (41).…”
mentioning
confidence: 58%
“…Genomic RNA of EMC virus also contains 5' VPg-pU (70). The VPg seems to prime poliovirus and EMC virus RNA synthesis because there is a significant amount of abortive VPg-pU and of VPg-pU-containing short oligonucleotides in picornavirus-infected cell lysates (71). The mRNAs of poliovirus isolated from the polysomal fractions at the middle and late stage of infections, however, do not contain 5' covalently bound proteins but start with 5' pU (72).…”
Section: B Viral Mrnasmentioning
confidence: 99%